DIVERSIFICATION STRATEGY OF WAJO SILK CONCENTRIS WEAVING - Karta Karta; Abdul Azis Said; Dian Cahyadi (TANRA: Jurnal Desain Komunikasi Visual Fakultas Seni dan Desain Universitas Negeri Makassar, 2019)
Sengkang silk weaving has stagnated in production due to the dynamics of similar product invasion at lower prices and related to fashion tastes that are constantly changing, and product diversification efforts as a marketing strategy have also been adopted. But the results are less encouraging. Learn from this experience and research has been carried out regarding various blockages that are factors. So try concentric diversification strategic efforts to overcome these problems in the form of dummy-analog in the form of studies in this study. This study aims to conduct a review related to these strategic steps. It is hoped that direction will be obtained so that the Sengkang silk industry can survive the onslaught in the free market era (MEA). The method used is data collection, assessment modeling and system development, and evaluation of finished products.